A case report and insightful review of congenital insensitivity to pain with anhidrosis - Prazad, Amal; Mathews, Aswathy (International Journal of Research in Medical Sciences, 2025)
We present a case of a 9-month-old male, born to a third-degree consanguineous marriage, presenting with a month-long history of mild to moderate fever occurring 3-4 times daily. The child remained active during afebrile periods and exhibited no associated symptoms. Physical examination revealed pallor and multiple abrasions on bilateral fingers, with stable vital signs. Extensive investigations for infectious and hematological conditions were negative. Notably, the child did not cry during IV insertion and the fever developed after sun exposure. A detailed CNS examination revealed an absence of sensation to crude touch, pain and temperature, leading to further tests which confirmed the diagnosis of congenital insensitivity to pain with anhidrosis (CIPA). This case underscores the importance of considering CIPA in children with unexplained fevers and insensitivity to pain, particularly in consanguineous families and highlights the need for regular follow-ups and supportive management.